Preliminary inflow and infiltration study of sewerage systems from two residential areas in Kuantan, Pahang / Hiew Thong Yap - Yap, Hiew Thong; Ngien, Su Kong; Othman, Norasman; Ahmad Abdul Ghani, Nadiatul Adilah; Abd Rahman, Norhan (Universiti Teknologi Mara Cawangan Pulau Pinang, 2017)
Sewerage system is the sole infrastructure which conveys sewage to sewerage treatment plants. The usage of a sewerage system should be optimized at the design stage to enhance environmental protection and human health. Wastewaters flows are produced from domestic sewage whereas inflow and infiltration come from surface runoff and groundwater. The purpose of this study is to identify inflow and infiltration in sewerage systems around Kuantan. This study was conducted in residential catchments at Taman Lepar Hilir Saujana and Bandar Putra with population equivalent of 1253 and 1694, respectively. ISCO 674 Rain Gauge was used to measure rainfall intensity. ISCO 2150 and 4250 Area Velocity Flowmeters were collected wastewater flowrate data which measured at 5-minute intervals and analyzed separately for wet and dry period. Infiltration rate was obtained by comparing the upstream flow and downstream flow from the two selected manholes. Based on the result, the average infiltration rate of Qpeak and Qave was 13.7% and 21.2% higher than the 5% and 10% stated in Hammer and Hammer. Inflow and infiltration is a concern and more comprehensive studies are needed to initiate the review of a revised infiltration rate that is more relevant to the future climate.